Optimizing MaxEnt to project habitat shifts of Idesia polycarpa var. vestita Diels, a bioenergy tree, in China under climate change scenarios - Yixuan Peng; Longcheng Jiang; Jin Wang; Rou Ma; Hua Lin; Evgeny Lopatin; Yangzhou Xiang; Hongyan Yang; Yuan Li (Biomass and Bioenergy, 2027)

1-MCP maintains postharvest quality of fresh lotus seeds by modulating ethylene signaling, phenolic metabolism, and starch metabolism - Hongyan Lu; Haizhen Si; Xueting Liu; Qiong Lin; Hongru Liu; Yang Yi; Hongxun Wang; Ting Min (Postharvest Biology and Technology, 2026)

Novel biallelic LSS variants in autosomal recessive hypotrichosis simplex: insights from a multi-omics approach - Xiaxia Liu; Kai Liu; Yuda Wei; Yongzhen Qi; Yangyang Luo; Tingli Chen; Xiaohua Ye; Junxu Lu; Yunjia Li; Liangqian Jiang; Juan Teng; Xingzhu Geng; et al. (Human Genetics, 2026)

Sulfonated dopamine interlayer-regulated positively charged polyamide membrane for phosphoric acid purification - Mingyang Lin; Xinghe Li; Junming He; Zheng Chen; Jingxing Wu; Hongyan Pan (Journal of Environmental Chemical Engineering, 2026)

Continuous flow-through electrochemical pretreatment for fouling control in ultrafiltration-based wastewater reclamation - Weichen Zeng; Yunan Gao; Dachao Lin; Hongyan Sun; Diannan Huang; Xueding Jiang; Zhi Dang; Hailong Wang (Chemical Engineering Journal, 2026)

Ecotoxicoproteomic assessment of the effects of phthalate esters on coastal phytoplankton (Gymnodinium sp.): From physiological inhibition to molecular acclimation - Kun Lin; Yanru Wang; Hongyan Xu; Liju Tan; Jianlei Chen; Ting Zhao; Jiangtao Wang (Marine Pollution Bulletin, 2026)

Pt nanoparticles as electron mediators in CdS/AgIn(WO4)2 nanotube heterojunctions for efficient photocatalytic hydrogen evolution - Quanmei Zhou; Jiayi Meng; Yifan Liao; Yuchen Wei; Bite Deng; Yuying Hu; Hongyan Zhao; Yakun Song; Mohan Zhang; Wei-Lin Dai (Chemical Engineering Journal, 2026)

Engineered norfloxacin-derived carbonized polymer dots for synergistic antibacterial and anti-inflammatory periodontitis therapy - Xinyu Jiang; Yu Deng; Jia Liu; Huan Chen; Hongyan Lin; Yu Zhong; Junjun Liu; Xinchan Liu; Bai Yang (Chemical Engineering Journal, 2026)

A two-layer safe reinforcement learning framework for multi-constraint reservoir operation: Integrating action masking and lagrangian dual method - Zaichao Xie; Xiaoli Zhang; Wei Xu; Guoguo Lin; Dong Li; Shuncai Zhang; Hongyan Chen; Sheng Yang (Journal of Hydrology, 2026)

Agmatine induces mitophagy via the PTS-I2R pathway to increase autophagic flux and attenuate sepsis-induced intestinal epithelial cell apoptosis - He Jin; Shuangqin Yin; Yongming Li; Xiangwei Hou; Lin Qiao; Tianyin Kuang; Jing Zhou; Xue Yang; Wanting Zeng; Chao Fan; Li Luo; Lihui Wang; et al. (Inflammation Research, 2026)

Multimodal detection of microplastics in human kidney stones and multi-omics exploration of renal cell metaflammation - Qingli Zeng; Jinhui Tang; Leilei Zhan; Ruiyin Liang; Chuanli Yang; Ruibin Cai; Jieyu Luo; Jia Xu; Tao Liu; Hongyan Wei; Lin Che (Journal of Hazardous Materials, 2026)

Hierarchically porous UiO-66-(OH)2@COF-OMe composites with multiple binding sites for synergistic extraction of polybrominated diphenyl ethers from surface waters - Jingpu Tang; Wentao Lan; Hongyan Zeng; Chenchen Lin; Xiaoping Wu (Journal of Hazardous Materials, 2026)

Mechanisms of core browning in ‘Yali’ pears during shelf life: insights from integrated physiological and transcriptomic analyses after prolonged cold storage - Jingling Dai; Hongyan Zhang; Ying Li; Xiaohui Lin; Bing Deng; Liya Liang (Food Bioscience, 2026)

Species-specific effects and trophic transfer of selenium in a freshwater food chain - Hongyan Lin; Yixuan Luo; Lixia Li; Fangli Wu; Hongxing Chen; Lingtian Xie (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Deep visual multi-omics reveals intra-tumor heterogeneity of gene expression and immunophenotype in colorectal cancer - Shijun Lei; Wanshan Ning; Hongyan Zhang; Qun Chen; Luming Xu; Shaobo Tian; Xiaoqiong Li; Wenyu Liu; Mengxi Xiang; Feng Liu; Guobin Wang; Lin Wang; et al. (Science Bulletin, 2026)

Visible light driven S-type heterojunction of g-C3N4/BiOBr for efficient degradation of six high-molecular-weight pollutants with various chromophores - Yifan Wei; Jiacheng Luo; Wenjing Luo; Hongyan Zhai; Xiao Liu; Ze Xu; Qinghua Ouyang; Na Lin (Journal of Environmental Chemical Engineering, 2026)

Polysaccharide-based ROS-responsive micro/nanomotors loaded with β-Carotene: Characterization, encapsulation, and enhanced antioxidant application - Fanghan Li; Linghui Li; Songyi Lin; Minghao Zeng; Hongyan Wang; Jiaxin Qiang; Yue Tang; Simin Zhang (Food Bioscience, 2026)

VFLING: Vertical Federated Learning for Multi-Omics Data Integration with Graphs - Xiaoli Li; Qi Li; Dedao Lu; Yue Lin; Saba Aslam; Huijun Li; Zequn Zhang; Yuxi Chen; Ruey-Song Huang; Hongyan Wu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Quercetin-loaded polysaccharide micro/nanomotors: enzyme-driven propulsion mechanism and targeted uric acid reduction performance - Zhiyu Yan; Hongyan Wang; Songyi Lin; Jiayi Qiao; Xiuping Dong; Fanghan Li; Xiaomeng Ren; Mingxian Zhang; Yifei Dong; Simin Zhang (Chemical Engineering Journal, 2026)

Effects of low-temperature vacuum frying on scallops quality and development of a machine learning-based quality prediction model - Haiyou Dong; Songyi Lin; Xiuping Dong; Bo Liu; Hongyan Wang; Simin Zhang (Food Control, 2026)

Molecular engineering for bitterness masking of natural products: from decoding structure-taste relationships to structure-driven bitterness suppression - Linjie Tian; Jiao Song; Jiaxin Li; Jing Wu; Haozhou Huang; Junzhi Lin; Li Han; Hongyan Ma; Dingkun Zhang (Critical Reviews in Food Science and Nutrition, 2026)

Schaftoside inhibits neuroinflammation and exerts antidepressant effects through METTL3-mediated m6A modification of circ_0001470 sponging miR-183-5p to regulate MAP3K1 expression - Haohao Wang; Jinxiang Wu; Keren Ma; Ting Su; Qiyan Lin; Hongyan Zhang; Teng Ma; Pan Wang; Dong Liu (Psychopharmacology, 2026)

PRDX6 as a Ferroptosis-Related Hub Gene in the Entorhinal Cortex of Alzheimer’s Disease: A Multidimensional Bioinformatics and Experimental Validation Study - Xiaolin Li; Ziteng Man; Tiantian Cheng; Juan Song; Yanan Bao; Yu Lin; Hongyan Yang (Journal of Molecular Neuroscience, 2026)

Removal of Mg2+ and Al3+ from high-concentration wet-process phosphoric acid by NH4MgAlF6 complexation-precipitation - Ran Zhu; Zili Wang; Yangyang Luo; E. Yang; Shisong Yang; Qian Lin; Hongyan Pan; Zheng Chen (Journal of Environmental Chemical Engineering, 2026)

A microenvironment-responsive chitosan based injectable hydrogel with synergistic anti-inflammatory effects of triptolide and copper ions for spinal cord injury repair - Han-Jian Hu; Zhenming Tian; Zeng-Lin Li; Chun Cheung Chan; Hongyan Zhang; Shipeng Tang; Yu Chen; Zhaoyin Chen; Tian Hu; Bin Liu; Gang-Biao Jiang (Carbohydrate Polymers, 2026)

Modulation of viscosity, swallowability, and stability of starch-based thickener: The effect of konjac gum and xanthan gum - Haoran Fan; Lin Sun; Xiaodan Liu; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2026)

Instant gel-forming microcapsules based on micronized-κ-carrageenan for bitter taste quenching bioinspired by the passion fruit seed - Jiao Song; Linjie Tian; Shuyu Deng; Yifei Zhang; Junzhi Lin; Zhiping Guo; Hongyan Ma; Dingkun Zhang; Li Han; Zhimin Ci (Carbohydrate Polymers, 2026)

Adiponectin Signaling Ameliorates Cognitive Dysfunction in Type 2 Diabetic Mice by Activating the Hippocampal AdipoR2-PPARα/CREB Pathway - Hongyan Gong; Yanli Liu; Liu Xia; Bochao Niu; Jian Kong; Bin Wang; Xu Lin; Lin Lin; Yanlin Bi (Molecular Neurobiology, 2026)

From plant-based food waste to biochar: A green strategy for agri-food supply chain waste valorization–a comprehensive review - Xuejiao Chen; Yanbo Hao; Wei Lin; Liya Xie; Rui Yang; Wenliang Xiang; Zhilian Gong; Feng Gu; Hongyan Liu; Jie Tang (Trends in Food Science & Technology, 2025)

Microcystis aeruginosa copes with toxic effects of micro/nano-plastics with varying particle sizes through different self-regulatory mechanisms - Zihan Lin; Ting Wang; Fuxun Ai; Xiaolin Wang; Ying Yin; Hongyan Guo (Aquatic Toxicology, 2025)

Enzymatic resistance of starch-polyphenol inclusion complexes: polyphenol inhibition and structural changes during in vitro digestion - Haoran Fan; Lin Sun; Xu Yao; Yangyang Wen; Xuesong Xiang; Hongyan Li; Jing Wang; Baoguo Sun (Carbohydrate Polymers, 2025)

The association between exposure to phthalates and cardiovascular disease: A comprehensive study utilizing NHANES data from 2005 to 2018 and network toxicology - Wei Gong; Hongyan Zhu; Xinran Sun; Jinxiu Zhang; Meiyun Lin; Peng Sun (Chemico-Biological Interactions, 2025)

PRDM14 promoted NSCLC cell proliferation, migration and invasion via modulating H3K27me3-mediated PEBP1/Raf-1/MEK/ERK MAPK signaling - He Shi; Yunfei Jiang; Haijun Mu; Guohua Liu; Xinyue Cheng; Weili Kong; Xingqi Zhou; Xiaoqiang Wen; Xiao Wang; Yiyu Lin; Linyu Pan; Haiying Dong; et al. (Genes & Genomics, 2025)

Effects of Triphenyl phosphate (TPHP) on Microcystis aeruginosa: Growth stimulation and adaptability mechanisms - Mengyuan Mei; Lin Deng; Zihan Lin; Fuxun Ai; Ying Yin; Hongyan Guo (Journal of Hazardous Materials, 2025)

High-precision radiocarbon dating and carbon reservoir effect of a maar lake in South China - Yao Gu; Huayu Lu; Hongyan Zhang; Pengyu Lin; Xiaoyi Dong; Yao Wang; Shuangwen Yi; Fuzhi Lu; Fan Yang (Quaternary Geochronology, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Fluorescence-enabled portable droplet microfluidic paper-based analytical device for rapid and sensitive biotoxicity assay - Demian I. Njoku; Wanqing Dai; Jiayu Chen; Yaru Gao; Hongyan Sun; Guozhu Mao; Yung-Kang Peng; Jian Lin Chen (Journal of Environmental Chemical Engineering, 2025)

Tree-ring dating of the construction of the Yinshan tomb in Shaoxing, Zhejiang Province: A preliminary study - Shiyuan Shi; Congcong Xiao; Zebin Li; Yongxiang Wang; Hui Wang; Zhansheng Niu; Hongyan Zhang; Pengyu Lin; Xinrui Liu; Lingling Lu; Jiangfeng Shi; Huayu Lu (Science China Earth Sciences, 2025)

Effects of elevated atmospheric carbon dioxide to Microcystis aeruginosa under different forms of phosphorus sources - Juanjuan Zhang; Wenxuan Xu; Qingquan Zhang; Lin Deng; Fuxun Ai; Ying Yin; Hongyan Guo (Chemosphere, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Human Amniotic Epithelial Stem Cells Promote Functional Recovery After Spinal Cord Injury In Rats By Regulating The Polarization Of Macrophages - Hongyan Zhang; Jingjing Liu; Beike Chen; Xin Chen; Shijun Wei; Guanghui Zhang; Xiaomin Yan; Xingsen Xue; Guangjian He; Jiangkai Lin; Hua Feng; Weihua Chu (Molecular Neurobiology, 2025)

A simple and colorimetric method utilizing cell-free toehold switch sensors for the detection of Chlamydia trachomatis, Ureaplasma urealyticum and Neisseria gonorrhoeae - Fengling Fang; Hongyan Guo; Zhaopei Guo; Lin Lin; Lu Lai; Yue Shi; Weiquan You; Shanjian Chen; Can Liu; Mingming Zhao; Shaobin Guo; Qishui Ou; et al. (Analytica Chimica Acta, 2025)

An assessment of the psychologically restorative effects of the environmental characteristics of university common spaces - Hongyan Wen; Hanzheng Lin; Xiao Liu; Weihong Guo; Jiawei Yao; Bao-Jie He (Environmental Impact Assessment Review, 2025)

A flame-retardant and weakly solvated gel electrolyte for high-performance and high-safety Ah class sodium-ion batteries - Lixing Xue; Hongyan Pan; Yuejun Wang; Zhengyi Wang; Xuhui Wang; Qian Lin; Kuo Zhang; Xiangnan Bu; Maohui Bai; Bo Hong (Chemical Engineering Journal, 2025)

Bactericide adsorption by purple soil modified by decomposed liquid and humic substance from Bischofia javanica - Hongyan Deng; Xiuying Ma; Mah Noor Fatima; Wenbin Li; Jing Lin; Nanxi Li; Zhifeng Liu (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Molecular insights into the anti-spoilage effect of salicylic acid in Favorita potato processing - Wenhua Wang; Liping Hong; Zhijun Shen; Mingqiong Zheng; Hongyan Meng; Ting Ye; Zhikai Lin; Lianghua Chen; Ying Guo; Enming He (Food Chemistry, 2024)

A low-molecular-weight α-glucan from edible fungus Agaricus blazei Murrill activates macrophage TFEB-mediated antibacterial defense to combat implant-associated infection - Qishan Wang; Yuehong Wang; Yihao Liu; Kai Yuan; Yixuan Lin; Xian Qian; Hongyan Pei; Liangliang Weng; Kaijian Fan; Yihe Hu; Yiqi Yang (Carbohydrate Polymers, 2024)

Core-shell structured composite high-efficiency catalyst Co@Pd/TiO2 with a compressed-strain Pd shell for the direct synthesis of H2O2 - Feifei Hu; Meng Wang; Xin Zhou; Shisong Yang; Xuan Chen; Chaochuang Yin; Qian Lin; Hongyan Pan; Zheng Chen (Chemical Engineering Journal, 2024)

Bismuth-based material with alveolar-like structure as advanced anode for superior potassium storage - Lu Cheng; Yangyang Tang; Haoxiang Lin; Yingjuan Sun; Hongyan Li (Chemical Engineering Journal, 2024)

Functionality developments in montmorillonite nanosheet: Properties, preparation, and applications - Wei Wang; Liming Wu; Lin Chang; Wenshuai Yang; Liang Si; Hongyan Nan; Weijun Peng; Yijun Cao (Chemical Engineering Journal, 2024)

Defect engineering of sulfur vacancies in vanadium disulfide integrated with graphene as advanced potassium-ion battery cathode - Haoxiang Lin; Zhenxiang Wang; Jinghua Quan; Hongyan Li (Chemical Engineering Journal, 2024)

Allelopathy of extracellular chemicals released by Karlodinium veneficum on photosynthesis of Prorocentrum donghaiense - Hongyan Xu; Yanru Wang; Kun Lin; Liju Tan; Jiangtao Wang (Journal of Hazardous Materials, 2024)

DOTAD: A Database of Therapeutic Antibody Developability - Wenzhen Li; Hongyan Lin; Ziru Huang; Shiyang Xie; Yuwei Zhou; Rong Gong; Qianhu Jiang; ChangCheng Xiang; Jian Huang (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Effect of ultraviolet aged polytetrafluoroethylene microplastics on copper bioavailability and Microcystis aeruginosa growth - Juanjuan Zhang; Zihan Lin; Fuxun Ai; Wenchao Du; Ying Yin; Hongyan Guo (Aquatic Toxicology, 2024)

Effect of nitro-substituted ending group on the photovoltaic and photocatalytic performance of non-fullerene acceptors - Jing Wang; Junwei Zhu; Chenxi Li; Yi Lin; Xiang Li; Hongyan Zhang; Zaifei Ma; Yan Lu (Chemical Engineering Journal, 2024)

In vivo transgenic studies confirm the critical acylation function of LeBAHD56 for shikonin in Lithospermum erythrorhizon - Liu Yang; Changyi Wang; Xiaohui Lai; Suo Jin; Xuan Wang; Zhongling Wen; Minkai Yang; Aliya Fazal; Yuhang Ding; Zhongyi Li; Jinfeng Cai; Guihua Lu; et al. (Plant Cell Reports, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

Amorphous nanoscale antimony-vanadium oxide: A high capacity anode material for potassium ion batteries - Yuanji Wu; Haoxiang Lin; Hongyan Li (Chemical Engineering Journal, 2024)

Influence of goethite nanophase on rare-earth element patterns and enrichment in marine phosphates during early diagenesis - Jieqi Xing; Shan Li; Hongyan Wei; Jiaxin Xi; Xiaoju Lin; Yiping Yang; Haiyang Xian; Wei Tan; Jingming Wei; Jianxi Zhu (Chemical Geology, 2024)

Characteristics of the atmospheric boundary layer height: A perspective on turbulent motion - Jinhong Xian; Hongyan Luo; Chao Lu; Xiaoling Lin; Honglong Yang; Ning Zhang (Science of The Total Environment, 2024)

Engineered Bacillus subtilis Biofilm@Biochar living materials for in-situ sensing and bioremediation of heavy metal ions pollution - Xiaojuan Zhu; Qinyuan Xiang; Lin Chen; Jianshu Chen; Lei Wang; Ning Jiang; Xiangrui Hao; Hongyan Zhang; Xinhua Wang; Yaqian Li; Rabia Omer; Lingfan Zhang; et al. (Journal of Hazardous Materials, 2024)

Cooling has stimulated soil carbon storage in forest ecosystems - Meta Francis Justine; Pan Kaiwen; Zebene Tadesse; Zhou Hongyan; Zhang Lin (Environmental Research, 2024)

Construction of highly sensitive electrochemical immunosensor based on Au and Co3O4 nanoparticles functionalized Ni/Co bimetal conductive MOF for quantitative detection of HBsAg - Yifan Li; Wenda Wang; Wangxiang Yue; Qian Lei; Zhenting Zhao; Yongjiao Sun; Hongyan Xu; Wendong Zhang; Lin Chen; Jung Kyu Kim; Jie Hu (Chemical Engineering Journal, 2024)

p-Toluenesulfonic acid enhanced neutral deep eutectic solvent pretreatment of soybean straw for efficient lignin removal and enzymatic hydrolysis - Wenxuan Wu; Peiwen Zhu; Liping Luo; Hongyan Lin; Yuheng Tao; Lingyu Ruan; Liqun Wang; Qing Qing (Bioresource Technology, 2024)

The ultramicropore biochar derived from waste distiller’s grains for wet-process phosphoric acid purification: Removal performance and mechanisms of Cr(VI) - Kai Su; Guotao Hu; Tianxiang Zhao; Huinan Dong; Yi Yang; Hongyan Pan; Qian Lin (Chemosphere, 2024)

Organic matter enrichment in shale deposited proximal to paleo-uplifts and its impact on shale gas exploration - Donglin Lin; Zhaodong Xi; Shuheng Tang; Gary G. Lash; Qiulei Guo; Hongyan Wang; Yanming Zhu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Multi-omics integration analysis of long-distance drifting process of green tides in the Yellow Sea simulated in a large-volume flowing water system - Xue Yang; Hongyan Xu; Kun Lin; Liju Tan; Jiangtao Wang (Science of The Total Environment, 2023)

Effect of bentonite and composite-modified carbonized fiber on Cu(II) and Cr(VI) adsorption by purple soil - Wenbin Li; Lin Luo; Bixia Wang; Hongyan Deng; Tianjiang Jin; Zhifeng Liu (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Discovery and verification of bitter components in Panax notoginseng based on the integrated strategy of pharmacophore model, system separation and bitter tracing technology - Jing Yang; Min Qiu; Tai Lu; Shangdong Yang; Ji Yu; Junzhi Lin; Hongyan Ma; Zhiping Guo; Zhencai Chen; Xue Han; Dingkun Zhang (Food Chemistry, 2023)

Assessing the potential risks, sources and the relationship between the dissolved and particulate polycyclic aromatic hydrocarbons (PAHs) in the typical semi-enclosed bay, Bohai Bay of China - Kun Lin; Rui Wang; Liju Tan; Shan Jiang; Hongyan Xu; Yali Cao; Jiangtao Wang (Marine Environmental Research, 2023)

Dynamic characteristics of refrigerant and lubricant in R290 rolling piston compressor of low-temperature air to water heat pump (LT-AWHP) during defrosting cycle - Hongyan Shi; Ning Sun; Wei Yang; Bowen Lei; Jie Lin; Jianhua Wu (International Journal of Refrigeration, 2023)

Facile preparation of nitrogen-doped microporous carbon from potassium citrate/urea for effective CH4 separation and uptake - Li Zhang; Yonggang Dong; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Yongyong Shi; Yutao Lv; Cuiwei Zhang; Hongyan Pan; Qian Lin (Fuel, 2023)

Paleofire dynamics in response to climate change during late Miocene derived from microcharcoal records in the Weihe Basin - Lin Zhao; Huayu Lu; Hanlin Wang; Hongyan Zhang; Fang Lei; Lingyu Tang (Quaternary International, 2023)

Impact of dietary zinc on the growth performance, histopathological analysis, antioxidant capability, and inflammatory response of largemouth bass Micropterus salmoides - Hongyan Kou; Xueting Liu; Junru Hu; Gang Lin; Yufan Zhang; Li Lin (Fish & Shellfish Immunology, 2023)

Electronic regulation and hydrophobicity improvement of the palladium active site by ionic liquid to achieve high selectivity direct synthesis of hydrogen peroxide - Lang Wu; Hong Qin; Songhua Zhou; Ziming Luo; Yang Xiao; Huan You; Qian Lin; Hongyan Pan; Keliang Wang (Chemical Engineering Journal, 2023)

Self-assembled synthesis of Pd/SPEn from polyelectrolyte membranes for efficient direct synthesis of H2O2 via inhibiting the dissociation of O − O bond - Entong Ye; Zheng Chen; Yongyong Shi; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Quansheng Wu; Qian Lin; Hongyan Pan; Keliang Wang (Chemical Engineering Journal, 2023)

Higher impact resistance and lower antibiotic resistance genes proliferation rate in shortcut nitrification-denitrification process under long-term antibiotics selection pressure - Chong Yang; Zhouliang Tan; Lin Wang; Hongyan Zhang; Wenwei Li; Fan Wang; Xin Li; Houzhen Zhou; Yangwu Chen (Chemical Engineering Journal, 2023)

Integrated metabolomics and transcriptomics analyses reveal the key genes regulating differential metabolites of longissimus dorsi muscle in castrated South Sichuan black goats (Capra hircus) - Nanchi Zhang; Feng Xu; Li Wang; Quzhe Emu; Yong Wei; Lin Zhang; Yuan Xu; Jingsheng Fan; Yan Sun; Shuobu Shama; Hongyan Zhou; Chunmei Li; et al. (Functional & Integrative Genomics, 2023)

Multiple genotypes infection and molecular characterization of Torque teno neovison virus: A novel Anelloviridae of mink in China - Weizhi Xin; Zhiyuan Guo; Lin Wang; Yifan Li; Haikun Shangguan; Kun Xue; Hongyan Chen; Hongliang Yang; Lili Zhao; Junwei Ge (Research in Veterinary Science, 2023)

Effective conversion of corn stalk into ethyl levulinate and crude lignin catalyzed by ionic liquids - Xiaoqi Lin; Kaisen Jiang; Xuebin Liu; Hongyan Bi; Tianya Li; Dezhi Han; Qinqin Zhang (Biomass and Bioenergy, 2023)

Connecting the Gut Microbiota and Neurodegenerative Diseases: the Role of Bile Acids - Shixu Wang; Chongchong Xu; Hongyan Liu; Wei Wei; Xuemei Zhou; Haipeng Qian; Li Zhou; Haiqing Zhang; Li Wu; Chen Zhu; Yuting Yang; Lin He; et al. (Molecular Neurobiology, 2023)

Tracing surface seawater mixing and nutrient transport by 222Rn on the northern coast of Beibu Gulf, China - Hao Wang; Qiangqiang Zhong; Fule Zhang; Suiyuan Chen; Hongyan Bao; Jing Lin; Dekun Huang; Tao Yu (Acta Oceanologica Sinica, 2023)

Aging process does not necessarily enhance the toxicity of polystyrene microplastics to Microcystis aeruginosa - Di Wu; Lin Deng; Ting Wang; Wenchao Du; Ying Yin; Hongyan Guo (Science of The Total Environment, 2023)

Bearing characteristics of mono-column composite bucket foundation in sand for offshore wind turbines - Puyang Zhang; Xin Qi; Hongyan Ding; Conghuan Le; Yifeng Lin; Jiandong Xiao (Ocean Engineering, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Thin-layer chromatography coupled with HPLC-DAD/UHPLC-HRMS for target and non-target determination of emerging halogenated organic contaminants in animal-derived foods - Ying Li; Ling Wang; Minggang Zheng; Yongfeng Lin; Hongyan Xu; Aifeng Liu; Yi Hua; Yuqing Jiang; Ke Ning; Shanmin Hu (Food Chemistry, 2023)

Impact of environmental factors on diversity of fungi in sediments from the Shenzhen River Estuary - Wenzhen Lin; Xin Liu; Linfeng Gong; Ruzhen Liu; Minghuang Ling; Chiming Guo; Hongyan Meng; Zhuhua Luo; Xiaona Du; Ying Guo; Wei Xu (Archives of Microbiology, 2023)
In this study, to explore the relationship between environmental factors and fungal diversity in the Shenzhen River ecosystem, multiple methods including chemical analysis, culture isolation, qPCR analysis of fungal ITS region and ITS-based Illumina next-generation-sequencing were integrated. A total of 115 isolates were finally isolated and could be classified into 23 genera. Top three abundant genera isolated were Meyerozyma (18 strains), Aspergillus (17 strains) and Penicillium (14 strains). Based on the Illumina sequencing approach, 829 OTUs were affiliated to seven phyla, 17 known classes, and 162 genera, indicating the Shenzhen estuary sediments are rich in fungal diversity. The major fungal genera were Meyerozyma , Trichoderma and Talaromyces . Environmental factors showed a gradient change in Shenzhen estuary, and fungal abundance was only significantly correlated with NH 4 + . Shannon index was significantly correlated with pH and IC ( P

Divergent responses and ecological risks of wheat (Triticum aestivum L.) to cerium oxide nanoparticles in different soil types - Dun Chen; Zihan Lin; Fuxun Ai; Yan Xia; Wenchao Du; Ying Yin; Hongyan Guo (Science of The Total Environment, 2023)

Exploring the driving factors of haze events in Beijing during Chinese New Year holidays in 2020 and 2021 under the influence of COVID-19 pandemic - Lining Luo; Xiaoxuan Bai; Yunqian Lv; Shuhan Liu; Zhihui Guo; Wei Liu; Yan Hao; Yujiao Sun; Jiming Hao; Kai Zhang; Hongyan Zhao; Shumin Lin; et al. (Science of The Total Environment, 2023)

Melanin from Sepia pharaonis ink alleviates mucosal damage and reduces inflammation to prevent alcohol-induced gastric ulcers - Lin Liu; Kuan Lu; Jingwen Xie; Hongxia Che; Hongyan Li; Xie Wancui (Food Bioscience, 2023)

Understanding and revealing the intrinsic impacts of the COVID-19 lockdown on air quality and public health in North China using machine learning - Yunqian Lv; Hezhong Tian; Lining Luo; Shuhan Liu; Xiaoxuan Bai; Hongyan Zhao; Kai Zhang; Shumin Lin; Shuang Zhao; Zhihui Guo; Yifei Xiao; Junqi Yang (Science of The Total Environment, 2023)

Enhanced soil respiration, vegetation and monsoon precipitation at Lantian, East Asia during Pliocene warmth - Kexin Wang; Huayu Lu; Carmala N. Garzione; Lin Zhao; Chenghong Liang; Shuyue Li; Daniel O. Breecker; Fang Lei; Hongyan Zhang (Climate Dynamics, 2022)

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

Construction of an egg-like DTAB/SiO2 composite for the enhanced removal of uranium - Tuckyun Cheang; Hongyan Zhou; Weihao Lin; JiaJun Zheng; Liang Yu; Yongcheng Zhang (Environmental Science and Pollution Research, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Dynamics of antibiotic resistance genes and microbial community in shortcut nitrification–denitrification process under antibiotic stresses - Chong Yang; Lin Wang; Huan Wang; Hongyan Zhang; Fan Wang; Houzhen Zhou; Zhouliang Tan; Yangwu Chen (Environmental Science and Pollution Research, 2022)

Bearing Characteristics of Helical Pile Foundations for Offshore Wind Turbines in Sandy Soil - Yifeng Lin; Jiandong Xiao; Conghuan Le; Puyang Zhang; Qingshan Chen; Hongyan Ding (Journal of Marine Science and Engineering, 2022)
Helical pile foundations are a new foundation type for offshore wind power applications with high bearing capacity and good recovery that can be quickly and easily constructed. In this study, the finite element method was used to simulate the bearing characteristics of helical pile foundations after installation. For simulations, a blade, deeply buried in a single layer of sand, was selected. Through numerical simulations, the vertical bearing characteristics of a single helical screw pile and an ordinary pile without blades were compared, and the compression and uplift characteristics of the helical pile were revealed. In addition, the effects of pitch, blade diameter, inclination angle, number of blades, and blade spacing on the bearing characteristics of a single helical pile were analyzed. The results show that the single helical pile has the highest bearing capacity and bearing efficiency when the pitch is 0.02 times the blade buried depth, the blade diameter is 2.5 times the pile diameter, the multi-blade spacing is more than two times the blade diameter, and the number of blades is less than or equal to three. However, compared with the straight pile, the vertical bearing capacity of the single inclined helical pile did not improve significantly.

Emerging role of exosomal long non-coding RNAs in lung cancer - Lulu He; Minmin Lin; Jing Shen; Hongyan Qi (Molecular Biology Reports, 2022)

High-throughput sequencing clarifies the spatial structures of microbial communities in cadmium-polluted rice soils - Li Song; Zhenzhi Pan; Yi Dai; Lin Chen; Li Zhang; Qilin Liao; Xiezhi Yu; Hongyan Guo; Guisheng Zhou (Environmental Science and Pollution Research, 2021)

Overexpression of uracil permease and nucleoside transporter from Bacillus amyloliquefaciens improves cytidine production in Escherichia coli - Ruoshuang Ma; Haitian Fang; Huiyan Liu; Lin Pan; Hongyan Wang; Heng Zhang (Biotechnology Letters, 2021)

Study on the Molecular Mechanisms Against Human Breast Cancer from Insight of Elemental Distribution in Tissue Based on Laser-Induced Breakdown Spectroscopy (LIBS) - Hongyan Wei; Zhao Zhao; Qingyu Lin; Yixiang Duan (Biological Trace Element Research, 2021)

The origin of arc basalts: New advances and remaining questions - Yigang Xu; Qiang Wang; Gongjian Tang; Jun Wang; Hongyan Li; Jinsheng Zhou; Qiwei Li; Yue Qi; Pingping Liu; Lin Ma; Jingjing Fan (Science China Earth Sciences, 2020)

Effects of carboxymethyl chitosan on the growth and nutrient uptake in Prunus davidiana seedlings - Dandi Xu; Hongyan Li; Lijin Lin; Ming’an Liao; Qunxian Deng; Jin Wang; Xiulan Lv; Honghong Deng; Dong Liang; Hui Xia (Physiology and Molecular Biology of Plants, 2020)

Climate warming alters subsoil but not topsoil carbon dynamics in alpine grassland - Juan Jia; Zhenjiao Cao; Chengzhu Liu; Zhenhua Zhang; Li Lin; Yiyun Wang; Negar Haghipour; Lukas Wacker; Hongyan Bao; Thorston Dittmar; Myrna J. Simpson; Huan Yang; et al. (Global Change Biology, 2019)
Subsoil contains more than half of soil organic carbon (SOC) globally and is conventionally assumed to be relatively unresponsive to warming compared to the topsoil. Here, we show substantial changes in carbon allocation and dynamics of the subsoil but not topsoil in the Qinghai‐Tibetan alpine grasslands over 5 years of warming. Specifically, warming enhanced the accumulation of newly synthesized ( 14 C‐enriched) carbon in the subsoil slow‐cycling pool (silt‐clay fraction) but promoted the decomposition of plant‐derived lignin in the fast‐cycling pool (macroaggregates). These changes mirrored an accumulation of lipids and sugars at the expense of lignin in the warmed bulk subsoil, likely associated with shortened soil freezing period and a deepening root system. As warming is accompanied by deepening roots in a wide range of ecosystems, root‐driven accrual of slow‐cycling pool may represent an important and overlooked mechanism for a potential long‐term carbon sink at depth. Moreover, given the contrasting sensitivity of SOC dynamics at varied depths, warming studies focusing only on surface soils may vastly misrepresent shifts in ecosystem carbon storage under climate change.

Effects of mutual grafting on cadmium accumulation characteristics of first post-generations of Bidens pilosa L. and Galinsoga parviflora Cav. - Hongyan Li; Jin Wang; Lijin Lin; Ming’an Liao; Xiulan Lv; Yi Tang; Xun Wang; Hui Xia; Dong Liang; Wei Ren; Wei Jiang (Environmental Science and Pollution Research, 2019)

Developmental retardation due to paternal 5q/11q translocation in a Chinese infant: clinical, chromosomal and microarray characterization - Xiangyu Zhao; Hongyan Xu; Chen Zhao; Lin Li (Journal of Genetics, 2019)

Regulation of mitochondrial NAD pool via NAD+ transporter 2 is essential for matrix NADH homeostasis and ROS production in Arabidopsis - Lilan Luo; Yajun He; Yannan Zhao; Qian Xu; Jian Wu; Haiyan Ma; Hongyan Guo; Lin Bai; Jianru Zuo; Jian-Min Zhou; Hong Yu; Jiayang Li (Science China Life Sciences, 2019)

De novo transcriptome sequencing and identification of genes related to salt stress in Eucommia ulmoides Oliver - Lin Wang; Hongyan Du; Tiezhu Li; Ta-na Wuyun (Trees, 2018)

Identification and expression analysis of the Eucommia ulmoides farnesyl diphosphate synthase gene family to reveal the key gene involved in rubber biosynthesis - Lin Wang; Teng Jing; Tiezhu Li; Hongyan Du; Ta-na Wuyun (Acta Physiologiae Plantarum, 2018)

Ground-based radar reflectivity mosaic of mei-yu precipitation systems over the Yangtze River–Huaihe River basins - Yali Luo; Weimiao Qian; Yu Gong; Hongyan Wang; Da-Lin Zhang (Advances in Atmospheric Sciences, 2016)

Complete chloroplast genome sequences of Eucommia ulmoides: genome structure and evolution - Lin Wang; Ta-na Wuyun; Hongyan Du; Depeng Wang; Deming Cao (Tree Genetics & Genomes, 2016)

RKIP Regulates Neural Cell Apoptosis Induced by Exposure to Microwave Radiation Partly Through the MEK/ERK/CREB Pathway - Hongyan Zuo; Tao Lin; Dewen Wang; Ruiyun Peng; Shuiming Wang; Yabing Gao; Xinping Xu; Li Zhao; Shaoxia Wang; Zhentao Su (Molecular Neurobiology, 2015)

Isolation and characterization of 18 microsatellite loci in the Chinese Noctule bat, Nyctalus plancyi - Hao Liu; Yujie Ran; Hongyan Shi; Xiaodong Jia; Lin Zhao (Conservation Genetics Resources, 2015)

Response of water resources to climate change and its future trend in the source region of the Yangtze River - Lin Li; Hongyan Shen; Sheng Dai; Hongmei Li; Jianshe Xiao (Journal of Geographical Sciences, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Response of runoff to climate change and its future tendency in the source region of Yellow River - Lin Li; Hongyan Shen; Sheng Dai; Jianshe Xiao; Xinghe Shi (Journal of Geographical Sciences, 2012)

The expression of Na, K-ATPase in Litopenaeus vannamei under salinity stress - Hongyan Sun; Lvping Zhang; Chunhua Ren; Chang Chen; Sigang Fan; Jian Jun Xia; Hongjun Lin; Chaoqun Hu (Marine Biology Research, 2011)

A Simple and Neutral Receptor Acting as a Sensitive and Switch-on Fluorescent Chemosensor for H2PO 4 − - Weiwei Huang; Hongyan Su; Sikai Yao; Hai Lin; Zunsheng Cai; Huakuan Lin (Journal of Fluorescence, 2011)

Occurrence and distribution of polycyclic aromatic carbons in sludges from wastewater treatment plants in Guangdong, China - Xiangying Zeng; Zheng Lin; Hongyan Gui; Wenlan Shao; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Environmental Monitoring and Assessment, 2010)

A New Fluorescent Chemosensor Detecting Co2+ and K+ in DMF Buffered Solution - Xiuli Wang; Wenyan Zheng; Hongyan Lin; Guocheng Liu (Journal of Fluorescence, 2010)

Isolation and characterization of a gene encoding cinnamate 4-hydroxylase from Parthenocissus henryana - Shujun Liu; Yuanlei Hu; Xiaoli Wang; Li Han; Songquan Song; Hongyan Cheng; Zhongping Lin (Molecular Biology Reports, 2009)

Genetic and physical localization of an anthracnose resistance gene in Medicago truncatula - Shengming Yang; Muqiang Gao; Shweta Deshpande; Shaoping Lin; Bruce A. Roe; Hongyan Zhu (Theoretical and Applied Genetics, 2007)

High glucose promotes the production of collagen types I and III by cardiac fibroblasts through a pathway dependent on extracellular-signal-regulated kinase 1/2 - Mengxiong Tang; Wei Zhang; Huili Lin; Hong Jiang; Hongyan Dai; Yun Zhang (Molecular and Cellular Biochemistry, 2007)

A deletion mutation in the ?A1/A3 crystallin gene (CRYBA1/A3) is associated with autosomal dominant congenital nuclear cataract in a Chinese family - Yanhua Qi; Hongyan Jia; Shangzhi Huang; Hui Lin; Jingzhi Gu; Hong Su; Tieying Zhang; Ya Gao; Lijun Qu; Dandan Li; Ying Li (Human Genetics, 2004)